Clinical value of high‐resolution dynamic contrast‐enhanced (DCE) MRI in diagnosis of cutaneous squamous cell carcinoma. Issue 4 (3rd November 2020) - Tang, Mengxiao; Huang, Renjun; Chen, Jianhua; Sheng, Meiying; Zhang, Zhongshuai; Xing, Jianming; Guo, Lingchuan; Li, Yonggang
Abstract: Background: While uncomplicated cases of skin squamous cell carcinoma (cSCC) can be treated with surgery topical therapy alone, more objective and non‐invasive examination methods are needed to guide clinicians to make more detailed biopsy and surgical plans for lesions with atypical or subcutaneous growth. High‐resolution magnetic resonance imaging (HR‐MRI) is a novel skin imaging method. Materials and methods: Prospective collection of 19 patients with clinically suspected cSCC. All patients underwent high‐resolution DCE‐MRI using a 70‐mm microscopy coil before operation. The imaging features and results of surgical pathology were recorded. K trans, K ep, V e values, and the time‐signal curve (TIC) types were determined using DCE images. Results: 16 cases of cSCC, 3 cases of acanthoma. The subcutaneous invasion of all lesions was clearly displayed, of which 8 lesions invaded the subcutaneous fat layer, 5 invaded the muscle layer, 1 invaded the periosteum, 2 invaded the cap fascia, and the layer of all lesions invasion judged by HR‐MR imaging was consistent with the postoperative pathology. The main manifestations of cSCC were ill‐defined margin, obvious inhomogeneous enhancement, higher perfusion parameters value and type‐III TIC, while acanthoma showed well‐defined and type‐I TIC. Some imaging findings (such as boundary, enhancement) and DCE perfusion parameters of the two groups overlap. Conclusion: High‐resolution DCE‐MRI can fully and directly display the subcutaneous invasion of cSCC, and more work needs to be done to prove its value. Next, we will expand the sample size, and further explore its value in the differential diagnosis and prognosis evaluation of cSCC from acanthoma or other skin tumors.